Trends in prediabetes and diabetes prevalence and associated risk factors in Vietnamese adults - That Thanh Ton; Anh Thi Ngoc Tran; Ich Thanh Do; Hoa Nguyen; Thi Thanh Binh Nguyen; Minh Tu Nguyen; Van Anh Bao Ha; Anh Quoc Tran; Huu Khoi Hoang; Binh Thang Tran (Epidemiology and Health, 2020)
OBJECTIVES The prevalence of diabetes mellitus is rapidly increasing in Vietnam, particularly among adults aged over 45 years. This study estimated trends in diabetes and prediabetes prevalence and determined risk factors in Vietnamese adults (over 45 years). METHODS A cross-sectional study was conducted based on data from an annual diabetes screening program among people aged 45-69 years in an urban city in central Vietnam (Da Nang). Joinpoint regression analyses were performed to calculate the annual percentage change and ptrend-values. Multinomial logistic regression analysis was used to determine risk factors. RESULTS In total, 3,765 men and 9,149 women were included in this analysis. The age-adjusted prevalence of diabetes and prediabetes in 2017 was 11.4% and 52.9%, respectively. The prevalence of diabetes was higher in men (15.1%) than in women (10.3%), but that of prediabetes was similar in both genders (53.4% vs. 52.8%). The prevalence of prediabetes significantly increased during the study period, whereas no upward or downward trend for diabetes was observed. The prevalence of obesity, abdominal obesity, hypertension, and dyslipidemia showed no obvious trend. Obesity, a high waist-to-hip ratio, hypertension, more severe abdominal obesity, and dyslipidemia were significantly associated with a higher risk of diabetes and prediabetes. CONCLUSIONS Diabetes and prediabetes were more prevalent among people aged over 45 years than in the general population. Da Nang has experienced a marked increase in the prevalence of prediabetes. These findings have significant implications regarding the need for nationwide public health interventions and management aiming at diabetes prevention and control.